National pastime how Americans play baseball and the rest of the world plays soccer - Szymanski, Stefan, 1960- (Brookings Institution Press, 2005)
"Examines, from an economic perspective, how the different traditions of soccer and baseball have shaped the possibilites for their commercial organization and exploitation, and considers how each sport might learn from the other's experiences to develop meaningful reforms"--Provided by publisher.